Location Based Disaster Response Prioritization Using AHP and GIS: Prioritas Respon Bencana Berbasis Lokasi Menggunakan AHP dan GIS - Audy A. Kenap; Abigail A. Raranta; Glenn D. P. Maramis (Universitas Muhammadiyah Sidoarjo, 2026)
This study addresses structured decision-making in regional disaster management. General Background: Effective disaster management requires rapid and systematic prioritization to allocate limited emergency resources appropriately. Specific Background: In Minahasa Regency, disaster response prioritization at the Regional Disaster Management Agency (BPBD) has largely relied on rapid assessment and personal judgment, without systematic integration of spatial factors such as accessibility, affected population distribution, and proximity to public facilities. Knowledge Gap: Previous approaches commonly applied Analytic Hierarchy Process (AHP) or Geographic Information Systems (GIS) separately, limiting operational integration between multicriteria decision analysis and spatial information. Aims: This study aims to design and implement a web-based decision support system that determines location-based disaster response priority levels using integrated AHP and GIS. Results: The system applies hierarchical modeling, pairwise comparison, and consistency testing to generate weighted priorities based on disaster severity, affected population, impacted area, accessibility, and escalation potential. Interactive mapping enables spatial visualization of incidents and produces systematic, measurable priority classification compared to subjective assessment. Novelty: This research integrates AHP weighting and spatial analysis within an operational web platform applicable to BPBD Minahasa Regency. Implications: The system offers a quantitative and transparent foundation for data-driven disaster response prioritization at regional and broader administrative levels. Highlights Web-based platform integrates multicriteria weighting with spatial mapping for emergency handling.• Hierarchical modeling generates measurable urgency classification from structured criteria.• Interactive geographic visualization supports transparent allocation of limited resources. Keywords:Analytic Hierarchy Process; Geographic Information Systems; Disaster Response Prioritization; Decision Support System; Location Based System